NURSES’ KNOWLEDGE AND ATTITUDES TOWARDS DIETARY MANAGEMENT OF PATIENTS WITH DIABETES MELLITUS - MUHAMMAD, RG; SAFDAR, N; SHAHEEN, T (Biological and Clinical Sciences Research Journal, 2024)
Proper dietary management is crucial for patients with diabetes mellitus, and nurses play a key role in educating and managing these patients. Understanding nurses' knowledge and attitudes towards dietary management can help improve patient care. Objective: To assess the knowledge and attitudes of nurses towards dietary management of patients with diabetes mellitus. Methods: A cross-sectional study was conducted in the Nursing Department of Lahore General Hospital, Multan, from June 2023 to June 2024. A total of 150 nurses from medical and surgical wards were selected through convenience sampling. Data were collected using a self-administered questionnaire, which was anonymous and took 15-20 minutes to complete. The questionnaire was divided into three sections: demographic, social, and professional information; a modified version of the 20-item Nutritional Management of Diabetes Knowledge Test; and a 14-item Nurses’ Attitudes about Nutritional Management of Diabetes Questionnaire. Descriptive statistics were used to summarize the data, and Pearson’s correlation analysis was employed to explore the relationship between knowledge and attitudes. Results: The mean knowledge score among the nurses was 11.20 ± 1.90, with scores ranging from 5 to 17. After standardization, 90 nurses (60%) exhibited moderate knowledge of nutritional management for diabetes. The mean attitude score was 59.71 ± 5.98, with 129 participants (86%) demonstrating a favorable attitude. Pearson’s correlation analysis showed no statistically significant association between knowledge and attitude (r= -0.070, p= 0.419). Conclusion: The study found that nurses generally had moderate knowledge and a favorable attitude toward the dietary management of diabetic patients. These findings suggest a need for targeted educational interventions to enhance nurses' knowledge in this area, potentially improving patient outcomes.